Saving, investment and the net foreign asset position - Mathias Hoffmann (University of Cologne, Centre for Financial Research (CFR), 2005)
Over the last two decades, countries have exhibited net foreign assets and liabilities. This paper develops an empirical model to examine the causes for the stock of the net foreign asset positions in 51 developing and industrialised countries. The reasons for significantly high or low net foreign asset positions can be derived from long-run trend differences in saving and investment. Using cointegration techniques, it is shown that GDP per capita, public debt and demographic factors influence long-run saving and investment and, hence, net external wealth of developing and industrialised countries.
Keywords: C23; F41; G15; 330; Savings; Investment and Net Foreign Assets; Cointegrated Panel Data